Fronteira agrícola e conflitos territoriais nas Amazônias Brasileiras: a expansão do agronegócio da soja e seus efeitos no planalto de Santarém, Pará-Amazônia-Brasil - BARROS, Márcio Júnior Benassuly (Associação dos Geógrafos Brasileiros, 2020)
The research presented in this article aims to analyze the expansion of the agricultural frontier and the territorial confl icts generated by the arrival of soybeans on the Santarém plateau, in the state of Pará (Amazonia, Brazil). It is a case study, the methodology is based on two approaches: the synthesis of the literature and the fi eld work carried out over the past two decades. The research followed the following stages: state of the bibliographic art, fi eld work, focusing on direct observations, non-directive interviews with community members, local leaders, photographic archives, remote sensing and mapping. The main results show that the introduction of soybean in the municipality of Santarém, from 1996, led to deep territorial transformations, particularly for the communities lead into a territorial confl ict, faced with the expansion of the agricultural frontier.